Syntactic Networks of Interlanguage Across L2 Modalities and Proficiency Levels - Hao, Yuxin; Wang, Xuelin; Wu, Meng; Liu, Haitao (Frontiers in Psychology, 2021)
Over time, interlanguage studies have shifted from early qualitative to quantitative studies of specific linguistic structures. However, the focus of these studies is usually on one aspect of an interlanguage instead of the whole system. The ideal object of interlanguage research is a second language (L2) learner language system, for only in this way can the entire L2 learning process can be examined. As a self-organizing and self-regulated system, the panorama of interlanguage can be revealed objectively through a complex network approach. In this study, we construct eight interlanguage dependency syntactic networks of varying proficiency levels and modalities, and conduct a quantitative study of respective network parameters. We find that all syntactic networks of Chinese L2 learners (English native speakers) initially present scale-free and small-world properties. Additionally, there is no sudden syntactic emergence in interlanguage with different modalities. This suggests varying regularities in the development of a syntactic network between interlanguage and native language acquisition. Moreover, the first language plays an important role in L2 development. The network parameters (<k>), L, C, ND, and NC can differentiate interlanguage modalities, and five quantitative parameters, <k>, C, ND, γ′, and NC, can indicate L2 proficiency.